Ultra-fast automated brain volumetry based on bispectral MR imaging data - Friedlinger, Michael; Schröder, Johannes; Schad, Lothar R. (Computerized medical imaging and graphics, 1999)
In this paper we present a fast automated three-dimensional brain segmentation and brain volumetry method providing minimal requirements of the number of spectral MR image channels and the performance of the computer equipment employed. The presented method is based on standard non-iterative two-dimensional grey level segmentation techniques in combination with pixel vector-oriented classificators and morphological operators and requires a bispectral high resolution MR data base. In its current design, the method provides for the largely partial volume-corrected determination of the cerebrospinal fluid (CSF) and the white and grey brain matter volumes of the human brain. For the verification of our approach, the results of applications to clinical data were compared to those of studies found in the literature.
Gesehen am 25.01.2021